Living color : the biological and social meaning of skin color - Jablonski, Nina G. (London: University of California Press, 2012)
This book investigates the social history of skin color from prehistory to the present, showing how our body's most visible trait influences our social interactions in profound and complex ways. The author begins with the biology and evolution of skin pigmentation, explaining how skin color changed as humans moved around the globe. She explores the relationship between melanin pigment and sunlight, and examines the consequences of rapid migrations, vacations, and other lifestyle choices that can create mismatches between our skin color and our environment. Richly illustrated, this book explains why skin color has come to be a biological trait with great social meaning-- a product of evolution perceived by culture. It considers how we form impressions of others, how we create and use stereotypes, how negative stereotypes about dark skin developed and have played out through history. Offering examples of how attitudes about skin color differ in the U.S., Brazil, India, and South Africa, the author suggests that a knowledge of the evolution and social importance of skin color can help eliminate color-based discrimination and racism.
Biology -- Skin's natural palette -- Original skin -- Out of the tropics -- Skin color in the modern world -- Shades of sex -- Skin color and health -- Society -- The discriminating primate -- Encounters with difference -- Skin color in the age of exploration -- Skin color and the establishment of races -- Institutional slavery and the politics of pigmentation -- Skin colors and their variable meanings -- ; Aspiring to lightness -- Desiring darkness -- Living in color.
Includes bibliographical references and index.
Keywords: Human skin color; Human skin color -- Physiological aspects; Human skin color -- Social aspects; Human skin color -- Cross-cultural studies; Colorism